(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Due to the low manufacturing cost and ease of handling, ammonium nitrate-fuel oil (ANFO) is one of the most popular mining explosives. ANFO explosive is a typical representative of non-ideal explosives, which means that its detonation properties are strongly dependent on the charge diameter and the existence and properties of the confinement. In this work, the effect of different confining materials on the detonation properties of ANFO explosive is studied experimentally, and by hydrocode simulation by varying charge diameter, and the type and thickness of the confining materials. The results show that, along with the diameter of the charge, density and thickness of the confining material have a key impact on the detonation properties. An empirical confinement model, applicable in the range 0.3 < mC/mE < 15, is proposed. The model enables the estimation of detonation velocity of confined ANFO charges with a mean absolute percentage error (MAPE) of 14.25%.